Steamer CORWIN off Nome showing dogsled teams on ice hauling freight from ship, 1907 - Nowell, Frank H., 1864-1950
Caption on image: Dog team Hauling Freight from Steamer Corwin, Five miles out at Sea, Nome, Alaska. Printed on verso of image, l to r: No. 90589. Publ. by Portland Post Card Co., Portland, Ore. and Seattle, Wash. (Made in Germany.) Photo by F. H. Nowell. [stamp symbol at left corner reads:]Alaska-Yukon-Pacific Exposition Seattle 1909 Filed in Alaska--Transportation--Dog Team